Practicality Of Participatory Ergonomics And Teaching Factory Models In Metal Welding Training (Case Study At Batam Training School) - M. Ansyar Bora, Jalius Jama, Syahril (International Journal of Advanced Science and Technology, 2020)
This study aims to measure the practicality of the participatory ergonomic and teaching factory model in metal welding training in order to improve the abilities and skills of welding training participants at Batam Training School. This research is based on findings at the research location where the welding training target has not been achieved ie 400 hours of welder can be proficient in 5 welding positions. This research uses research and development (R&D) methods and ADDIE development procedures. Data analysis techniques used quantitative descriptive analysis techniques and qualitative validity. The results of the study were the practicality of the model meeting the practical criteria based on the instructor's response was 84% ​​and based on the training participants 86%. The application of the Participatory Ergonomics and Teaching Factory model in metal welding training can impacts the training participants, namely: 1) the ability to plan work, 2) the ability to analyze work, 3) the ability to perform work, 4) the ability to determine alternatives and how to complete the work well, 5) the ability to perform work on time, 6) the ability to evaluate work results, and 7) the ability to communicate.